2010
DOI: 10.12693/aphyspola.118.1047
|View full text |Cite
|
Sign up to set email alerts
|

Time Dependent Changes in Ag Doped YBCO Superconductors

Abstract: Magnetization measurements at 77 K were conducted on the single-crystalline samples of YBCO superconductor doped with Ag prepared by the top-seeded melt-growth process. The single-grain samples had a nominal composition Y 1.5 Ba 2 (Cu,Ag) 3 O y . Magnetization measurements on the samples, oxygenated by two different processes: by standard oxygenation and by high pressure oxygenation, repeated after 24 months, revealed time dependent changes in magnetization behaviour and critical transition temperatures, T c ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…The best known application is in the Magnetic Resonance Imaging (MRI) systems widely employed by health care professionals for detailed internal body imaging. Other prominent applications include the magnetically levitated trains without friction and electrical power transmission with no energy loss [2][3][4][5]. However, superconductors have superconductivity only at or below their transition temperature [6], which hold back the wide spread application of superconductors.…”
Section: Introductionmentioning
confidence: 99%
“…The best known application is in the Magnetic Resonance Imaging (MRI) systems widely employed by health care professionals for detailed internal body imaging. Other prominent applications include the magnetically levitated trains without friction and electrical power transmission with no energy loss [2][3][4][5]. However, superconductors have superconductivity only at or below their transition temperature [6], which hold back the wide spread application of superconductors.…”
Section: Introductionmentioning
confidence: 99%
“…As important functional materials, high-transitiontemperature (high-T C ) superconductors 1 have some typical physical parameters, such as transition temperature T C , magnetic susceptibility and critical current density (J C ), which make them very useful in many practical applications like magnetically levitated trains and power transmission. [2][3][4][5] Previous researches showed that the high-T C superconductors are generally characterized by a two-dimensional layered superconducting condensate with unique features that are not traditional superconducting metals. 6 Their important property, T C , is determined by their layered crystals, bond lengths, valency properties of the ions, and Coulomb coupling between electronic bands in adjacent, spatially separated layers.…”
Section: Introductionmentioning
confidence: 99%